Mapping Gerasa: a new and open data map of the site. (18th February 2019) - Lichtenberger, Achim; Raja, Rubina; Stott, David
Abstract: Abstract : This article presents a new and accurate map of Gerasa/Jerash, an important site located in modern northern Jordan, which displays urban development spread across more than two millennia.